Detecção e identificação elétrica dos nucleotídeos do DNA via nanoporo híbrido de grafeno e nitreto de boro hexagonal: um estudo teórico. - Souza, Fábio Arthur Leão de (2017)
In this thesis work, a novel architecture of solid-state nanopore in a hybrid two-dimensional (2D) material for detection and identification of biomolecules is proposed. The system is composed of a zigzag graphene nanoroad embedded in hexagonal boron nitride (h-BN). A theoretical study based on ab-initio calculations was carried out to assess its energetic stability, structural, electronic and transport properties. Our results indicate the capability of controlling by gate voltage the current pathways through the conducting graphene strip. Then, motivated by the recently developed electrochemical reaction (ECR) technique for fabricating nanopores in a highly controlled manner in 2D materials, and aiming to evaluate the possibility of drilling pores in the hybrid material, vacancy defect formation energies of carbon, boron and nitrogen were evaluated throughout different regions of the system. As a result, our findings suggest that it would be possible to drill a pore in graphene nanoroad from a carbon vacancy in the graphene/h-BN interface, keeping just a carbon chain between the pore and h-BN domain in the opposite interface. Accordingly, a pore of approximately 12.5Å in diameter with aforementioned characteristics was built. Therefore, to develop and assess the feasibility of such proposed device to act as nanosensor, a combination of density functional theory with non-equilibrium Green’s function methods were employed. Hence, investigations on how each nucleotide that forms DNA should modulate the local current at the nanopore device were performed, where four nucleotides were tested: deoxyadenosine monophosphate (dAMP), deoxyguanosine monophosphate (dGMP), deoxycytidine monophosphate (dCMP), and deoxythymidine monophosphate (dTMP). Analyses of the pore+nucleotide zero-bias transmission functions have revealed that it should be in principle possible to distinguish between all four nucleotides inside the nanopore setup, which should occur in practice by their sensitivity fingerprints in real-time conductance measurements. Furthermore, it was demonstrated that the mechanism of detection of the referred hypothetical sensor is governed by modulation of the conductance of the carbon chain running along the graphene/h-BN interface due to local dipole moments of the target molecule.